Strategi Pengembangan Agrowisata Bali Pulina di Desa Sebatu, Kecamatan Tegallalang, Kabupaten Gianyar - MAHADEWI, I.A. BINTANG MANIK; SURYAWARDANI, I.G.A.OKA; ANGGRENI, I.G.A.A. LIES (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Strategy Development of Bali Pulina Agrotourism in Sebatu Village, Tegallalang Sub-District, Gianyar Regency Bali Pulina Agrotourism is located in Desa Sebatu Village, at Tegallalang Sub District. Due to a lot of local agrotourism business nearby the Bali Pulina, make a increasement of fierce competition between each other to keep their existence. Sustainable of Bali Pulina Agrotourism is determines by the strategy concept of development in orther to overcome the uncertainty of visitors. The purpose of this research is to evaluate internal factor and external factor and also generate the alternative strategy to develop and make a longterm sustainability of Bali Pulina Agrotourism. The internal factor, external factor with matrix evaluation, matrix SWOT and QSPM are used in this field analysis. The result shown that the strength of internal factor to develop Bali Pulina Agrotourism is the area have good soil fertility to support the agrotourism sector development. Then, the weakness of internal factor is the lack of promotion such as on social media, newspaper, and magazine. Meanwhile, the opportunity of external factor that Bali Pulina have is the back to nature trend with the advantages of nature tour concept, religious, Balinese culinary and the strong Balinese culture that can promises by this agrotourism. The threat of the external factor that can be risk of Bali Pulina Agrotourism is the tight competition between nearby agrotourisms. Based on matrix SWOT analysis, there are eleven concern of alternative strategy with the priority strategy is to optimally using facilities in Bali Pulina Agrotourism.